2017
DOI: 10.4172/2375-4427.1000176
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary Investigation of the Relationship between the Temperament of Young Children Who Stutter and the Temperament of Their Parents

Abstract: Previous studies suggest temperamental differences between young preschool-age children who stutter and those who do not. It is also known that parental socialization plays a major role in the temperamental development of children. However, to-date, whether temperamental differences exist between parents of children who stutter and parents of those who do not is unknown. The nature of relational differences between parent-child temperament across talker groups is also unclear.The present preliminary study exam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 41 publications
0
2
0
Order By: Relevance
“…16 While in another study Anderson et al, 17 using Behavioral style questionnaire (BSQ), noted that CWS, more commonly showed temperamental with less distractibility, they were more non adaptable to change and showed irregular biologi-cal functions, with such characteristics acting to maintain and exacerbate stammering. 17 In contrast to these studies, Johnson and Karrass, 18 reported that no significant difference exist between temperament of CWS and CWNS as well as their parents.…”
Section: Discussionmentioning
confidence: 88%
“…16 While in another study Anderson et al, 17 using Behavioral style questionnaire (BSQ), noted that CWS, more commonly showed temperamental with less distractibility, they were more non adaptable to change and showed irregular biologi-cal functions, with such characteristics acting to maintain and exacerbate stammering. 17 In contrast to these studies, Johnson and Karrass, 18 reported that no significant difference exist between temperament of CWS and CWNS as well as their parents.…”
Section: Discussionmentioning
confidence: 88%
“…We wanted to examine whether the concept of temperament ties into the literature of dog-owner relationship, as it is widely utilized in e.g. parent-child literature 29,[37][38][39] , but no data exists on its effects in the field of human-dog interaction. Thus, we examined the human factors under the concept of temperament, utilizing the revised Adult Temperament Questionnaire (ATQ-R 26 ).…”
mentioning
confidence: 99%